Baseball America 2025 almanac - Cooper, J.J; Kaufman, King; Norris, Josh; Eddy, Matt (Matthew); Collazo, Carlos A.; Flaherty, Peter G.; Mates, Seth (Baseball America, 2025)
"It was another year to remember at all levels of baseball, and no book offers you a more complete recap of the season than the annual Baseball America Almanac, now in its 43rd edition. All the stories, all the statistics--from the major leagues to the minor leagues to college and high school ranks, no one covers the game more thoroughly than Baseball America. Now the only definitive baseball annual on the market, the Baseball America Almanac is better than ever. The 2025 Almanac is the best in the business. It has all the major league news and statistics, an overview of each organization's season, the minor league year in review, comprehensive college coverage, a full recap of the 2024 draft and foreign and winter league coverage." --